Hierarchical Modeling of the Liver Vascular System - Torres Rojas, Aimee M.; Lorente, Sylvie; Hautefeuille, Mathieu; Sanchez-Cedillo, Aczel (Frontiers in Physiology, 2021)
The liver plays a key role in the metabolic homeostasis of the whole organism. To carry out its functions, it is endowed with a peculiar circulatory system, made of three main dendritic flow structures and lobules. Understanding the vascular anatomy of the liver is clinically relevant since various liver pathologies are related to vascular disorders. Here, we develop a novel hepatic circulation model with a deterministic architecture based on the constructal law of design over the entire scale range (from macrocirculation to microcirculation). In this framework, the liver vascular structure is a combination of superimposed tree-shaped networks and porous system, where the main geometrical features of the dendritic fluid networks and the permeability of the porous medium, are defined from the constructal viewpoint. With this model, we are able to reproduce physiological results and to study changes in blood pressure and flow rates throughout the hepatic vasculature due to resection or damage in certain portions of the organ, simulated as deliberate blockages in the blood supply to these sections. This work sheds light on the critical impact of the vascular network on mechanics-related processes occurring in hepatic diseases, damage healing and regeneration that involve blood flow recirculation and are at the core of liver resilience.